A Comparative Study of Bilateral FTA/CEP Arrangements - John Lawrence V. Avila (Philippine Institute for Development Studies (PIDS), 2004)
This study is a comparative analysis of recently concluded bilateral free trade or closer economic partnership agreements including the Japan-Singapore Economic Partnership Agreement (JSEPA), the New Zealand-Singapore Closer Economic Partnership (NZSCEP), the United States- Singapore Free Trade Agreement (USSFTA), the Singapore-Australia Free Trade Agreement (SAFTA), and the Korea-Chile Free Trade Agreement (KCFTA). The primary objective here is to describe and analyze the structure and institutional aspects of these agreements. This paper draws out the general outlines of these bilateral accords looking into their defined principles, scope of preferences, system of rules, and other regime features. These five bilateral agreements are examined against their consistency with WTO, comprehensiveness defined in terms of the scope and depth of the agreement, the degree of flexibility defined in terms of coverage of exemptions given to members, and the level of institutionalization, referring to the organizational and implementing aspects of the agreement.
Keywords: 330; bilateral agreements; Japan-Philippines economic partnership; structural and institutional aspects of FTA/CEP; Internationale Wirtschaftsbeziehungen; Freihandelszone; WTO-Recht